COMPENSATION DELAY TIME OF MEASURING SIGNAL AT THE LEAKAGE CHANNEL OUTPOOT OF SPEECH INFORMATION - V. K. Zheleznyak; I. B. Burachonak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Evaluation method of security assessment a speech signal in information leakage channel under high-level noise with significant Bandpass flatness by complex measuring signal with a large base in equal intelligibility bands is proposed. Using the mathematical approach a derivative of cross-correlation function between complex measuring signal with a large base at the inlet and outlet channel speech information leakage allows to determine the position of the axis points in which derivative is zero. After that its time delay and frequency shift at the output of leakage channel of speech information within а minimum mean square error are determined. Compensation with time delay high accuracy and frequency shift complex measuring signal with a large base at the output of information leakage channel allowed to significantly improving the accuracy and sensitivity of the assessment of protection a speech signal in information leakage channel.